Historical Process and Its Subject in the Ontology of “All-Unity” - Raudeliūnas, Traidenis (Problemos, 1988)
L. Karsavin considered the relationship between the absolute being and the relative one to be the main philosophical and religious problem and has solved it in pantheistic way. The solution served for him as a basis for the philosophy of history. The latter contains some interesting ideas. The historic process is viewed here as continuous one, the mankind is considered as the subject of history, the knowledge of history is linked to the definite epoch, etc. The mentioned ideas were not fruitfully developed by L. Karsavin because the character and the main conclusions of his philosophy of history were a priori defined in his speculative ontology.